The Profile of Junior High School Students’ Creative Thinking Skills about Alternative Energy in Science Learning - Fitri Amaliyah; Supeno Supeno; Sri Wahyuni (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
The most crucial role of creative thinking skills for students is encouraged by way of thinking to prove the truth of an assessment formulation. Teachers need to know students’ creative thinking skill profile and fulfill each indicator level to generate focused ideal learning to improve creative thinking skills. This research was conducted to explore junior high school students’ creative thinking skill profile in science learning about alternative energy. This research is a quantitative descriptive essay test method. Respondents are 110 7th-grade junior high school students in Jember, East Java, Indonesia. The results showed that the creative thinking skills of junior high school students is low (44,98%). Students’ creative thinking skill still need to be developed. Some students find it challenging to design a unique creative work on alternative energy. We suggest that creative thinking skills need to improve by developing learning methods, models, strategies, approaches, media, context, and interaction in the discussion process.